Sustainable landscaping growing a greener home - Claudin, Craig; Mohl, Steve; Post, Robert (Green-ovating, home renovations for a sustainable world., 2010)
Shows how a green approach to landscaping can reduce the amount of energy needed to heat and cool a house, the proper management of rainwater and runoff, the value of native plants and the benefits of green roofs. Includes site vists with landscape architects and designers.